Thiol proteins in chromatin. Issue 3 (March 1986) - Ferraro, Anna; Giartosio, Anna; Eufemi, Margherita; Barra, Donatella; Altieri, Fabio; Turano, Carlo
Abstract : Total half-cystine residues in proteins of pig liver chromatin have been measured. About half of them are present in the reduced state. Thiol groups of non-historic chromatin proteins, which amount to about 40 nmol/mg of protein, are preferentially located in chromatin fragments which are more easily solubilised either by DNAse I or by DNAse II. The data obtained are compatible with an involvement of SH and SS groups in chromatin structure and function.